Dysfunctional Behavior Determinant Factors: Internal And Personal Characteristic Perspective - Fahruddin Z. Olilingo; Aditya Halim Perdana Kusuma Putra (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2021)
This study aims to analyze the effect of time budget pressure, task complexity, and personal characteristics of auditors either directly or with moderation on dysfunctional behavior. This study involved 56 auditors with the data collection method in a questionnaire. The study results stated that the four hypotheses were positively and significantly affected. In the direct testing stage, the impact of the task complexity variable is the most dominant variable with a powerful effect than the demonstration of the relationship involving the time budget pressure variable on dysfunctional behavior. Furthermore, in testing the moderation of personal characters, which moderate the relationship between task complexity and dysfunctional behavior, this is the most dominant variable.